Identifying biomechanical gait parameters in adolescent boys with haemophilia using principal component analysis. Issue 1 (17th November 2017) - Suckling, L. B.; Stephensen, D.; Cramp, M. C.; Mahaffey, R.; Drechsler, W. I.
Abstract : Introduction: Improvements in the medical management for those with haemophilia have resulted in improved clinical outcomes. However, current treatment regimens do not alleviate all joint haemarthroses with the potential for long‐term joint deterioration remaining. The evaluation of functional activities such as gait, using standardized tools to monitor children with haemophilia is emerging. Aim: This study explored differences in sagittal plane biomechanics of walking in adolescent boys aged 11‐18 years with haemophilia and an age‐matched group of typically developing boys. Methods: A motion capture system and 2 force platforms were used to collect sagittal plane kinematic, kinetic and temporal spatial data during level walking. Principal component analysis (PCA) was applied to kinematic and kinetic waveform variables. Group differences in temporal spatial and principal component scores for each kinematic and kinetic variable were evaluated using independent t tests. Results: Significant alterations ( P < .05) in temporal spatial and kinetic parameters were found in adolescent boys with haemophilia. Compared with typically developing adolescent boys, boys with haemophilia walked with reduced stance phase duration and altered pattern of external ankle joint moments during push off and the beginning of swing. Conclusion: The use of PCA rather than predetermined discriminatory variables provided additional insight into biomechanical alterations in adolescent boys with haemophilia, with adaptations occurring during terminal double support and early swing, affecting the ankle joint. This finding might be a key biomechanical marker that could be used to evaluate the joint function and the progression of early haemophilic arthropathy.